The NEW adventures of the digital vigilante! Facebook users' views on online naming and shaming. Issue 1 (March 2019) - Dunsby, Ruth M; Howes, Loene M
Increasingly, digital vigilante activity occurs via social media and can have negative consequences in the broader social world, a phenomenon that can be examined productively through a cultural criminological lens. One example of digital vigilantism is the online naming and shaming of people who are convicted or suspected of crime and subjecting them to embarrassment, harassment, and/or condemnation. To contribute to the prevention of negative impacts of online naming and shaming, this study aimed to better understand Australian Facebook users' views about – and experiences of participating in – online naming and shaming. Participants ( n  = 122) were primarily young Tasmanian adults who completed an online qualitative survey. Over one-quarter (26%) of participants reported having liked posts that name and shame a person suspected or convicted of crime, with smaller proportions engaging with these posts by sharing or commenting on them. Whilst Facebook users recognised the potential for online naming and shaming to impede justice, they perceived the practice as appropriate if it would foster community awareness and maintain community welfare. The findings are discussed in light of the roles of Facebook users' emotions, the social media as a cultural product, and the mediascape in constructing versions of reality. Practical implications of the study include the need for policing and media organisations to consider ways to meet their information needs without inadvertently encouraging acts of digital vigilantism. Overall, this study contributes to increased understanding of digital vigilantism and highlights the integral role of social media as a cultural product.